The effect of Kinesiology Taping on overload pains in employees of the Provincial Integrated Hospital in Toruń - Kałużna, Anna; Nasiewska, Anna; Kitschke, Ewa; Kałużny, Krystian; Żukow, Walery (Journal of Education, Health and Sport, 2018)
The aim of this study was to determine whether Kinesiology Taping is an effective method to combat lumbar spine related to overload, and how its application affected the pain of two professional groups of the hospital: administrative staff and medical personnel.The study included 80 employees of the Provincial Integrated Hospital in Toruń complaining of pain, related to overloading of the lumbar spine. Among the respondents there were 73 women, which accounted for 91% of the respondents and 7 men, which accounted for 9% of the respondents. The method that was used in the study was Kinesiology Taping. The numerical scale - NRS was used to assess the pain, with the help of which the subjects determined the level of their pain before the first application, during and after application. The fingers-floor test and the Schober test were used to determine changes in the mobility of the lumbar spine. Tests were performed before and after application.The case studies have shown that Kinesiology Taping is an effective method to combat lumbar spine pain.